Livelihoods, Wellbeing and the Risk to Life During Volcanic Eruptions - Barclay, Jenni; Few, Roger; Armijos, M. Teresa; Phillips, Jeremy C.; Pyle, David M.; Hicks, Anna; Brown, Sarah K.; Robertson, Richard E. A. (Frontiers in Earth Science, 2019)
A forensic analysis of fatalities and displacements from recent volcanic eruptions (1986-2015) provides insights into factors that influence actions to protect life in high-risk environments. Unlike many other geophysical hazard events, volcanic eruptions may be prolonged, and of variable intensity. This is reflected in patterns of volcanic fatalities. A global survey reveals that 63% of primary volcanic deaths occur after the first week of activity, with >44% of these deaths associated with citizens returning to an established high-hazard zone. Evacuations during volcanic eruptions are protracted and this allows time for competing pressures to arise. Examination of detailed data from three volcanic crises (Soufrière St. Vincent, Soufrière Hills, Montserrat and Tungurahua, Ecuador) suggests that the need to preserve livelihoods plays a strong role in protecting life. A dynamic, associated with pull (e.g. protecting assets, place attachment) and push factors (e.g. poor shelter conditions), can draw evacuees to return during high-risk periods. Similar considerations can restrain people with previous experience of volcanic hazards and displacement, from evacuating. Our global analysis shows that these pressures, when coupled with forecasting uncertainties and the rapid landscape change associated with volcanic eruptions, mean that the physical and social vulnerability of populations change significantly during the course of an eruption. Ongoing risk to life is shaped by hazard experience and action; timescales of hazard escalation and their relationship to warning and action; and the timescales over which evacuation conditions are tolerable to livelihood and asset preservation, and mental and physical wellbeing in shelters.